Learning Action Cell as A Channel for Teacher’s Professional Competence in Elementary Schools in the Divisions of Laguna - Liezl Ayuso Conde; Alberto D Yazon; Consortia S Tan; Marcial M Bandoy (Education Policy and Development, 2023)
This study investigated the relationship between the Learning Action Cell (LAC) level and teachers' professional competence. It utilized quantitative correlational design to assess and analyze the data of elementary teachers and how the LAC empowers and capacitates them on the various techniques and methodologies to be competent enough to deliver effective teaching facilitation. The 619 teachers respondents from nearby three (3) Schools Divisions were assessed on how LAC training every year improved their competencies. The finding proved that the more LAC sessions conducted, the higher the teacher’s competencies gained. The quantitative correlation denoted that the quality of implementation of the Learning Action Cell training based on the study result was very high. It visibly manifested in the total impact of LAC training is enhancing and empowering teachers' professional competencies. This study proved that it is an essential component of the education system as they provide a platform for collaboration, professional development, problem-solving, and continuous learning among teachers.